Prognostic Implications of Immature Platelet Fraction at 5-Year Follow-up Among ACS Patients Treated With Dual Antiplatelet Therapy - Karolina Gumiężna MD; Piotr Baruś MD; Grażyna Sygitowicz PhD; Agnieszka Wiśniewska PhD; Adrian Bednarek MS; Jakub Zabłocki MS; Adam Piasecki MS; Dominika Klimczak-Tomaniak MD, PhD; Janusz Kochman MD, PhD; Marcin Grabowski MD, PhD; Mariusz Tomaniak MD, PhD (SAGE Publishing, 2024)
Objective: Platelets are strongly associated with cardiovascular events due to their role in thrombotic processes. Reticulated platelets have higher prothrombotic potential. The aim of the study was to evaluate the effectiveness of immature platelet fraction (IPF) in predicting long-term clinical outcomes in patients with acute coronary syndrome (ACS). Methods: This prospective, observational study enrolled patients with ACS treated with dual antiplatelet therapy comprising acetylsalicylic acid and clopidogrel or ticagrelor. The primary outcome was a composite endpoint defined as major adverse cardiovascular events (MACE): all-cause death, myocardial infarction (MI), ischemic stroke, or unplanned revascularization. IPF was determined using flow cytometry in the first 24 h of hospitalization. MACE were evaluated by 2 physicians based on electronic databases and source documentation including discharge letters received from patients upon telephone contact. Results: Overall, there were 140 ACS patients (mean age 65.1 ± 11.7, 37 females [26.4%]) included in this study. Of them, 22.9% had diabetes mellitus, 69.3% hyperlipidemia, 25% had a history of MI. The median IPF values were 2.85 [1.8-4.2] %. Clinical follow-up (median time: 57 months [interquartile range 55-59 months]) was available for 130 patients (92.9%). MACE occurred in 27 patients (20.8%). There were higher rates of MACE at higher IPF tertiles (3rd vs 1st tertile: HR = 5.341 95% CI: 1.546-18.454, P  = .008). Cox regression analyses showed that IPF level was independently associated with MACE. Time-dependent receiver-operating characteristic curve analysis revealed area under the curve of 0.656 for 5-year outcome with an IPF cutoff point of 3.45% being 63.0% sensitive and 65.0% specific for MACE. Conclusions: The study showed IPF may be an independent predictor of long-term mortality and MACE (ClinicalTrials.gov number, NCT06177587).